Essential genetics and genomics - Hartl, Daniel L. (Burlington, MA : Jones & Bartlett Learning, 2020)
'Updated throughout to reflect the latest discoveries in this fast-paced field, Essential Genetics and Genomics, Seventh Edition, provides an accessible, student-friendly introduction to modern genetics. Designed for the shorter, less comprehensive course, the Seventh Edition presents carefully chosen topics that provide a solid foundation to the basic understanding of gene mutation, expression, and regulation. It goes on to discuss the development and progression of genetics as a field of study within a societal and historical context. The Seventh Edition includes new learning objectives within each chapter which helps students identify what they should know as a result of their studying and highlights the skills they should acquire through various practice problems'--Provided by publisher.
Machine generated contents note: -- Chapter1 The Genetic Code of Genes and Genomes. Chapter2 Transmission Genetics : Heritage from Mendel. Chapter3 The Chromosomal Basis of Heredity. Chapter4 Gene Linkage and Genetic Mapping. Chapter5 Human Chromosomes and Chromosome Behavior. Chapter6 DNA Structure, Replication, and Manipulation. Chapter7 The Genetics of Bacteria and Their Viruses. Chapter8 The Molecular Genetics of Gene Expression. Chapter9 Molecular Mechanisms of Gene Regulation. Chapter10 Genomics, Proteomics, and Genetic Engineering. Chapter11 The Genetic Control of Development. Chapter12 Molecular Mechanisms of Mutation and DNA Repair. Chapter13 Molecular Genetics of the Cell Cycle and Cancer. Chapter14 Molecular Evolution and Population Genetics. Chapter15 The Genetic Basis of Complex Traits. AppendixA Answers to Even-Numbered Problems. AppendixB Word Roots, Prefixes, Suffixes, and Combining Forms.
Preceded by Essential genetics / Daniel L. Hartl. 6th ed. 2014.
Includes index.
This book includes online access at www.jblearning.com, please refer library staff for the password.
Keywords: Genetic Phenomena; Genomics